The Process of Absorbing Arabic Sounds into the Sounds of the Minangkabau language: Phonological Study | ʿamaliyyat imtiṣāṣ al-ʾaṣwāt al-ʿarabiyyah fī ʾaṣwāt al-lughah al-mīnānjakābūiyyah: dirāsah fūnūlūjiyyah - suharmon, suharmon (Institut Agama Islam Negeri Palangka Raya, 2024)
This research explores the absorption of Arabic into the Minangkabau language, known as Minangization, focusing on the changes in vowel and consonant sounds. Using the agih method, which analyzes language through substitution, the study detects shifts in Arabic words within the Minangkabau language. Data analysisemploys translational equivalent techniques using both primary and secondary data. The findings reveal that most Minangkabau vocabulary derived from Arabic is absorbed through four patterns: dissimilation (similar sounds becoming less similar), diphthongization (single vowel sounds becoming diphthongs), anaptic (insertion of additional sounds), and zeroization, which includes apheresis (removal of phonemes at the beginning of a word), syncope (removal of phonemes in the middle), and apocope (removal of phonemes at the end). These findings facilitate Minangkabau students' study of both their native language and the Quran.